Analysis of Factors Affecting Psychological Resilience of Emergency Room Nurses Under Public Health Emergencies - Jiayun Lu BN; Pei Xu BN; Jinjin Ge MN; Haiyan Zeng BN; Weiqun Liu BN; Peifeng Tang BN (SAGE Publishing, 2023)
Resilience is essential for frontline health workers to cope with the unfavorable situations, especially under public health emergencies. Emergency room (ER) nurses are a special cohort of health professionals that may present moderate level of resilience. This study aimed to identify factors that are correlated with resilience in this special cohort to provide directions for intervention and management. ER nurses that have encountered a public health emergency within 3 months were recruited using purposive sampling and snowball technique for the study. Questionnaires, including Connor-Davidson Resilience Scale (CD-RISC), Zung Self-Rating Depression Scale (SDS), and Maslach Burnout Inventory-Human Services Survey (MBI-HSS) were established, followed by an in-depth interview to identify different clusters of themes. Thirteen ER nurses were recruited, and the average CD-RISC score was 66 ± 21. Resilience was negatively correlated with SDS index, and positively correlated with personal accomplishment. Five clusters of themes were identified from in-depth interviews, including physical tolerability, psychological tolerability, tenacity of internal drive, institutional implementation, and external adjustment. This study identified factors associated with resilience in ER nurses under public health emergencies, providing useful information for future directions for intervention.